Pengaruh Kompensasi Finansial dan Non Finansial terhadap Tingkat Turnover Intention pada Karyawan Generasi Z (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study aims to analyze the Effect of Financial and Non-Financial Compensation on Turnover Intention Levels in Generation Z Employees. Generation Z, known for its unique characteristics such as preference for work flexibility, technology, and work-life balance, shows a relatively high level of turnover intention compared to previous generations. Compensation is one of the important factors that can influence employees' decisions to stay or leave a company. This research method uses a quantitative approach with data collection techniques using questionnaires distributed to 50 Generation Z employees. Data were analyzed using classical analysis tests and multiple linear regression to determine the effect of compensation on turnover intention. The results showed that compensation had a significant effect on turnover intention, which means that the higher the level of compensation received, the lower the employee's desire to leave the company (Turnover Intention). These findings provide implications for human resource management to design a competitive compensation strategy that is in accordance with Generation Z's expectations in order to reduce turnover intention levels.